Proximal humeral endoprosthesis after tumor resection: does synthetic mesh improve stability? A radiographic review. Issue 3 (May 2019) - Chebli, Caroline M.; Letson, Douglas; Ruggieri, Pietro; Binitie, Odion
Abstract : Background: We proposed that aortograft aids in longer time to superior humeral migration and improved functional outcome measured as range of motion. Methods: A retrospective review from August 1, 1999 to December 30, 2015 identified 75 patients who received a proximal humeral endoprosthesis. The patients were divided into nonaortograft and aortograft groups. The final range of motion, the acromiohumeral interval (AHI) measured radiographically at each visit, the resection level, and the time to humeral migration above 7 mm were recorded. Results: Of the 75 patients identified, 17 patients were excluded due to lack of sufficient data or consistent follow-up. The average age of the 58 patients (55% male and 45% female) was 53.95 yr. Thirty-eight patients received aortograft and 20 patients did not. No difference in age or sex between the groups was noted. The average time to humeral head migration as defined by an AHI above 7 mm (superior migration) was 6.61 mo (SD=9.67) in the aortograft group and 4 mo (SD=4.33) in the nonaortograft group. This was not statistically significant ( P =0.717). There was no statistically significant difference in range of motion between the groups at final follow-up. Regarding resection level, there did not appear to be a difference in time to migration or final acromiohumeral interval. Conclusions: Historically, proximal humeral endoprostheses have a poor track record regarding stability. Although the aortograft group trended toward longer time to proximal humeral migration, it did not significantly improve functional range of motion. The role of modular reverse total shoulder arthroplasty should be further investigated to determine if there is improvement in stability and functional range of motion. Level of Evidence: IV.